Bali Smart Island: Smart City Implementation in Bali Province - Sanjaya, I Gede Wira; Darma, Gede Sri (Universitas Muhammadiyah Yogyakarta, 2023)
This study aims to explore and examine SPBE Towards Bali Smart Island in the Provincial Government of Bali. This study used a qualitative descriptive research method with an inductive approach. Data collection was carried out through interviews, observation, and documentation techniques. The results showed that SPBE towards Bali Smart Island has been going well and has implemented smart city development. However, ASN’s digital literacy and competence are still weak, post-pandemic regional budgets are not stable, cyberattacks, and the large number of application systems built by the center and each region are obstacles to implementing SPBE Towards Bali Smart Island. Strategies that can be implemented to overcome the obstacles encountered in implementing SPBE towards Bali Smart Island include: collaborating with pentahelix elements to hold local, national and global scale activities and events based on digital technology scale such as the Bali Digital Festival which is held every year; encouraging international investors to develop the digital technology industry in Bali so as to have a domino effect in developing smart city dimensions in realizing Bali Smart Island; forming an internal audit/assessor team to carry out periodic assessments related to SPBE development so as to create strong control and evaluation; optimizing the Cyber Lantern program using social media platforms in the form of providing training and sharing knowledge related to the use of digital technology, data security, technology ethics and so on as a medium for increasing digital literacy; forming the SPBE Forum throughout the Province of Bali to form integrated development of the Bali Smart Island program and hold training on the use of certified digital technology.